2017
DOI: 10.1159/000472257
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Treatment Concepts for Cutaneous T-Cell Lymphoma Based on Microenvironment Modulation

Abstract: Cutaneous T-cell lymphomas (CTCL) are a rare and biologically heterogeneous malignant entity comprising mycosis fungoides and Sézary syndrome as the most common subtypes. The current treatment outcome is characterized by high rates of relapse, but survival is usually not significantly shortened in low-stage disease. This is different in tumor-stage disease or aggressive CTCL subtypes where survival is significantly reduced. Recent advances have been made on several levels of tumor biology: Whole genome sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 82 publications
1
9
0
4
Order By: Relevance
“…Most of these GO terms involved genes that related to the immune microenvironment, including immune response, antigen processing, and presentation, as well as the interferon‐gamma‐mediated signaling pathway, suggesting that they are critical for the pathological mechanisms of CTCL. This was consistent with previous studies, which reported that many components, such as tumor‐associated macrophages, fibroblasts, and dendritic cells, as well as humoral factors, such as chemokines and cytokines, establish the tumor microenvironment and can regulate apoptosis, proliferation, and migration of CTCL . In the turquoise module, terms related to viral process, response to the virus and negative regulation of viral genome replication were found to have a significant role.…”
Section: Discussionsupporting
confidence: 91%
“…Most of these GO terms involved genes that related to the immune microenvironment, including immune response, antigen processing, and presentation, as well as the interferon‐gamma‐mediated signaling pathway, suggesting that they are critical for the pathological mechanisms of CTCL. This was consistent with previous studies, which reported that many components, such as tumor‐associated macrophages, fibroblasts, and dendritic cells, as well as humoral factors, such as chemokines and cytokines, establish the tumor microenvironment and can regulate apoptosis, proliferation, and migration of CTCL . In the turquoise module, terms related to viral process, response to the virus and negative regulation of viral genome replication were found to have a significant role.…”
Section: Discussionsupporting
confidence: 91%
“…This is most likely due to improved diagnostic techniques, growth and aging of the world population, the recent trends in the acquired immune deficiency syndrome (AIDS) epidemic, and the rising number of cancer-causing behaviors although the reasons behind this lymphoma epidemic are still poorly understood [ 1 ]. Despite a better understanding of the biology of lymphoma and many important therapeutic advances in lymphoma treatments in the past decade, improving the prognosis for patients with relapsed and treatment-resistant disease remains an important challenge [ 2 ]. In particular, a major hurdle on the road to the discovery and development of new drugs is the lack of adequate testing models.…”
Section: Introductionmentioning
confidence: 99%
“…We showed that this regimen was equally effective as intralesional administration reported by Theurich et al, although a low skin penetration at standard IV dosage has been reported. Moreover, parallel to B‐cells’ reduction, a significant decline in malignant T‐cell population was noted, supporting the central role of the former in tumor microenvironment and immunosurveillance, even in the setting of large cell transformation . Nevertheless, the optimal treatment for MF patients with high volumes of B‐cells should be further investigated.…”
Section: Discussionmentioning
confidence: 76%